2023
DOI: 10.3390/medicina59020309
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and Next-Generation Data Analysis for Identification of Genes and Molecular Pathways Involved in Subjects with Diabetes and Obesity

Abstract: Background and Objectives: A subject with diabetes and obesity is a class of the metabolic disorder. The current investigation aimed to elucidate the potential biomarker and prognostic targets in subjects with diabetes and obesity. Materials and Methods: The next-generation sequencing (NGS) data of GSE132831 was downloaded from Gene Expression Omnibus (GEO) database. Functional enrichment analysis of DEGs was conducted with ToppGene. The protein–protein interactions network, module analysis, target gene–miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 221 publications
0
11
0
Order By: Relevance
“…Therefore, understanding the pathological changes and molecular mechanisms of MS is essential for clinical diagnosis and treatment. Efficient NGS and bioinformatics analyses help us understand the molecular mechanisms of the disease onset and advancement, which is invaluable for biomarkers and therapeutic target identification [5152]. In our study, 959 DEGs were identified between MS patients and normal controls based on NGS dataset.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, understanding the pathological changes and molecular mechanisms of MS is essential for clinical diagnosis and treatment. Efficient NGS and bioinformatics analyses help us understand the molecular mechanisms of the disease onset and advancement, which is invaluable for biomarkers and therapeutic target identification [5152]. In our study, 959 DEGs were identified between MS patients and normal controls based on NGS dataset.…”
Section: Discussionmentioning
confidence: 96%
“…For diagnosis and treatment, it is necessary to further understand the molecular pathogenesis resulting in occurrence and advancement. Due to the advancement of NGS technology, the genetic modifications due to disease progression can be detected, indicating gene targets for diagnosis, therapy and prognosis of specific diseases [38-39].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, next generation sequencing (NGS) technology has been applied to the research on various bioinformatics, which can screen and identify genes and signalizing pathways of various diseases [1920]. NGS is an emerging molecular biology technology based on a high-throughput platform, which is widely used in COPD [21].…”
Section: Introductionmentioning
confidence: 99%